MEMORY’S LEARNING MODEL IMPLEMENT TO INCREASE MEMORY AND STUDYING ACHIEVEMENT MATHEMATICS - Mita Beti Umainingsih; Alexon Alexon; Nina Kurniah (UNIB Press, 2017)
The research commonly used to apply learning memory's to increase memory and students’ studying achievement mathematics. The Design of this research is Mixed Methods Research, which is mixed research method. MixedMethods Research used qualitative and quantitative elements. Exploratory sequential type started of Action research brazes. Action research brazes is performed in a few cycle until gotten by model suitably. Implementing memory's learning one that result of cycle 1 until cycle 3, applied at class III SDN 03 IPUH Mukomuko's regencies as classroom action research. Students learned memory at brazes to mathematics study experience step-up. Despitefully, student mastery to learning material also shows step-up. It points out that learning model implement memory's can increase student memory but also increase student mastery to learning material, although acquired step-up not as good as that expected but still on significant category. This research also results one learning model memory'sone that gets generic’s character, its mean that this learning model is enabled applicable on other school that have characteristic that equals to braze experiment in observational.Keywords: memory’s learning model, student memory, learning achievement mathematics